VOLATILITAS INDEKS KOMPOSIT PASAR MODAL ASEAN-3 - Anhar Fauzan Priyono (Quantitative Economics Journal, 2016)
Rapid integration between domestic and world economy in the last decade has been a major issue. For Indonesia, the situation has been accelerated by the adoption of floating exchange rate regime in 1997, also with the development of Indonesia stock exchange. One notable financial variable that often exposed to external shocks is stock market index. This research will analyzed the behavior of 3 major stock market indices in ASEAN, those are Jakarta Composite Index (JCI), Kuala Lumpur stock index (KLSE), and Singapore stock index (STI). The employment of volatility model is chosen to figured the behavior of those 3 indices, and to analyze the aggregate investment in each stock market. Observation will be based upon monthly basis, from 2010 until 2015.The findings in this research are (i) similarity in the movement behavior of ASEAN-3 stock market indices, (ii) Indonesia stock market shows the highest aggregate investment return relative to Malaysia and Singapore, (iii) Singapore stock market shows the lowest aggregate investment risk relative to Indonesia and Malaysia, as the representation of more developed stock market.